Effects of Social Network and Destination on Earnings and Economic Integration of Female Mexican Migrants - Gastón, María Teresa Teresa (Encuentro, 2013)
As immigrant contributions to the U.S. economy and society are debated, female migrants continue to increase their number in the U.S. work force. Little is known about the economic experiences of undocumented female Mexican migrants in the United States. Do women in traditional migrant destinations fare better than those in new destination cities, as has been shown for males? Does a strong social network positively impact earnings and participation in economic life? This study explores these questions with data collected at Mexican consulates in seven U.S. cities during 2004 and 2005 by Pew Hispanic Center field researchers. Controlling for education level and English fluency, social network and destination are examined for their effects on earnings and economic integration. The effects of social network on economic outcomes are also examined separately in new and traditional destinations. Evidence of the effect of education, English, social network, and destination on earnings and economic integration is consistent with previous findings for males, but nuances are found for this sample of female migrants that contributes to the literature. Experiences differ by destination with women in traditional migrant destination cities experiencing greater economic integration. Findings provide a rare glimpse into the economic experiences of undocumented female migrants in the U.S. Further research examining these factors after the recession and after increaseddeportations and anti-immigrant state and local ordinances is recommended.